Antoni Wyrwicz – professor of higher mathematics at the Vilnius university (1817–1831) - Gečiauskas, Evaldas (Lietuvos matematikos rinkinys, 2021)
Antoni Wyrwicz (1791–1865) was a professor of higher mathematics at the Vilnius university in the period from 1817 until 1831. Wyrwicz taught algebra by tractate of Sniadecki and Burdon, spherical trigonometry by Sniadecki, Cagnoli, Delambre Neper, astronomy by Delambre and Biot. Wyrwicz in 1819 published translation of Biot Analytical geometry. From 1824 until 1831 Wyrwicz taught differential and integral calculus by Lacroix and Lagrange. He translated 6 school books for algebra from Lacroix and 6 school books for geometry from Legendre.